Estudio de la incidencia de Barbary Plantae G2T, aplicado al suelo, en el rendimiento de dos híbridos de pepinillo (Cucumis sativus, L.), en la Comunidad de San Vicente de Pusir, Cantón Bolívar, Provincia del Carchi, 2017 - Montenegro Flores, María de los Ángeles (2018)
The present investigation was developed in the area of El Abejón, San Vicente de Pusir parish, Bolívar canton, Carchi province, located at: 0 ° 29'12,417 ", North latitude and 78 ° 2'16,387 West longitude at an altitude of 1700 meters above sea level The purpose of this investigation was to evaluate the yield of two gherkin hybrids (Cucumis sativus L.), subjected to three levels of Barbary plantae G2T, applied to the soil, in doses of 10.15 and 20 g / plant. The theoretical methods were used: Inductive-deductive, synthesis and experimental analysis, the design of Random Complete Blocks (DBCA) with factorial arrangement, (AxB) + 2,was used; for the statistical differences, the Tukey test was applied at 5% probability. The results obtained in the investigation, determined that the Jaguar Hybrid with a dose of 20g / plant presented the averages in height of plant, diameter of stem, number of fruits; while the hybrid Cobra with a dose of 20g / plant presented the highest yield in number of fruits and in weight, this being the A2B1 treatment; Cobra hybrid with different dose of 20 / plant was the most profitable the highest value of 22,886USD / ha.